Pengaruh Disiplin Kerja Terhadap Kinerja Pegawai Di Dinas Kesehatan Kabupaten Karawang - Chaerudin, Chaerudin; Umah, Aulia Wardatul (Peneliti.net, 2023)
This study aims to examine the effect of work discipline on employee performance at the Karawang District Health Office. The method used in this study is a quantitative method and uses descriptive and verification analysis, the sampling technique uses non-probability sampling, namely saturated sampling with a sample of 108 respondents. Testing is assisted by using the SPPS tool. The coefficient of determination shows the influence of work discipline on employee performance at the Karawang District Health Office of 38.8% while the remaining 61.2% is influenced by other factors not examined in this study. This study concluded that work discipline has a significant influence on employee performance at the Karawang District Health Office.